2007
DOI: 10.1016/j.soilbio.2007.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and substrate quality of leaf litters and fine roots from three exotic plantations and a native forest in the southwestern highlands of Ethiopia

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 41 publications
6
58
0
6
Order By: Relevance
“…72 ppm, corresponding to secondary carbinol C (i.e. C-2, C-3 and C-5 of pyranoside rings) in cellulose and hemicellulose (Almendros et al, 2000;Keeler et al, 2006;Lemma et al, 2007;Conte et al, 2010). Resonances at ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…72 ppm, corresponding to secondary carbinol C (i.e. C-2, C-3 and C-5 of pyranoside rings) in cellulose and hemicellulose (Almendros et al, 2000;Keeler et al, 2006;Lemma et al, 2007;Conte et al, 2010). Resonances at ca.…”
Section: Resultsmentioning
confidence: 99%
“…In all samples, a maximum peak in the carboxyl C region at ca. 172 ppm indicated the presence of carboxylic acids, amides and esters originating from compounds such as cutin, proteins and hydrolysable tannins (Lemma et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis showed that initial tissue chemistry explained the greatest proportion of variance in decomposition rate (85%), while environmental variables, most notably temperature, precipitation and actual evapotranspiration (AET) played a secondary role. Since Silver and Miya's analysis, fine root decomposition studies have largely focused on the effects of litter quality on rate of decay and generally support the notion that litter quality regulates microbial activity and thus decomposition (Chen et al 2001;Lemma et al 2007). In general, decay rates of fine roots are positively correlated with initial concentrations of Ca, Mg, Mn, N and P and negatively correlated with C:N, lignin:N, cellulose, and phenolic compounds including tannins, and lignin (Berg et al 1998;John et al 2002;Jalota et al 2006;Wang et al 2010;Tong et al 2012;García-Palacios et al 2016;Guerrero-Ramírez et al 2016;Roumet et al 2016).…”
Section: Factors That Influence Fine Root Decompositionmentioning
confidence: 95%
“…Later stages of decomposition are thought to be more heavily influenced by interactions between N content and chemical form and components of root cell walls including lignin, cellulose, and suberin (John et al 2002;Yang et al 2004;Tripathi et al 2006;Lemma et al 2007). Increases in soil N availability can suppress decomposition of phenolic compounds contained within cell walls (Berg 2000;Wang et al 2004).…”
Section: Factors That Influence Fine Root Decompositionmentioning
confidence: 99%
“…Changes in soil properties, in particular increases in the concentration of toxic minerals, can also affect the decomposition of organic residue, since they affect the structure and activity of microbial communities in the soil [19,20]. The physical and chemical properties of the soil are known to influence microbial communities [21].…”
mentioning
confidence: 99%